The Influence of Science Comics Learning Media and Problem-Based Learning Methods on the Effectiveness of Support Solution Learning for Students of SMAN 1 Toraja Utara - Sulpa Dewi Rantetampang; Bernadetha Nadeak; Mesta Limbong (Universitas Ahmad Dahlan, 2023)
Education is one of the spearheads of a country's success. In education, the teacher is the spearhead; for this reason, the teacher must continue to improve himself to innovate and be creative in presenting the material being taught so that learning objectives can be adequately achieved. One is in chemistry learning, which must motivate students to continue developing critical thinking skills. For this reason, through this thesis, the writer will examine